THE USE OF THE NOTION OF HUMANITY IN FRENCH LAW - Bioy, Xavier (Journal International de Bioéthique et d'Éthique des Sciences, 2015)
The lawyers little informed about the specificities of the French law often wonder about the use of the concept of dignity and about that of humanity who accompanies hit. This article makes a point on the sense give to this "humanity" which "is at one" with the subject of right.